Novel Intravenous Nanoemulsions Based on Cannabidiol-Enriched Hemp Oil—Development and Validation of an HPLC-DAD Method for Cannabidiol Determination - Agnieszka Sobczak; Piotr Zieliński; Anna Jelińska; Aleksandra Gostyńska-Stawna (Molecules)
Background: Intravenous nanoemulsions (NEs) are gaining attention as potential delivery systems for poorly water-soluble substances like cannabidiol (CBD). This study aimed to develop novel NEs based on CBD-enriched hemp oils and evaluate their physiochemical properties. Methods: The stability of hemp oils enriched with various concentrations of CBD (0.5%, 1.0%, and 1.5%) with and without the addition of α-tocopherol was determined, and the most stable oils were subsequently incorporated into NEs. In order to determine the CBD content in the obtained CBD-enriched oils and NEs, as well as to conduct stability tests, a new HPLC method was developed and validated. Results: The HPLC method demonstrated very good linearity, precision, accuracy, specificity, and robustness, enabling reliable assessment of the quality of newly developed formulations. The formulated NEs were characterized by droplet size of below 200 nm and polydispersity index PDI ≤ 0.14 satisfactory for intravenous application. Conclusion: This research presents a preliminary study on the development of CBD-enriched hemp oil-based NEs that showed promising potential for further investigation. A new HPLC-DAD method was appropriate to register changes in CBD concentration in various matrices, including CBD-hemp oil and intravenous NEs during their preparation and storage. Additionally, the effect of certain emulsifiers used in NE formulations on the course of the chromatographic analysis of CBD was examined, providing valuable insights concerning the application of the provided methodology in future formulation analysis.